Traditional fermented foods of Benin Republic: microbiological safety and health benefts - ZANNOU, Oscar; CHABI, Ifagbémi Bienvenue; KPOCLOU, Y. Euloge; KAYODE, A. P. Polycarpe; GALANAKIS, Orion Fausto; SELLI, Serkan (My University, 2023)
A wide range of traditional fermented foods is produced and prized in communities in developing countries. Due to the generation of benefcial microorganisms, nutritional and bioactive compounds such as organic acids, antioxidants, enzymes, vitamins, minerals, high bioavailable proteins, peptides, mannans, β-glucans and amino-acids, fermentation has been considered one of most vital food processing techniques to improve product shelf life, quality, and safety. The presented overview of scientifc research emphasizes the microfora potential and multifold advantageous efects of the fermented foods traditionally produced in the Benin Republic. Several innovative scientifc investigations on fermentation and fermented products, together with indigenous knowledge and professional experience, have been explored and discussed. The characterization of microbiological aspects of these foods revealed that they present economic, nutritional, and health advantages with essential prebiotics and probiotics for the indigenous communities. Furthermore, traditional fermented foods have high safety and quality. However, the industrial way is suggested to limit the eventual adverse contaminations
Keywords: Fermented foods · Prebiotics · Probiotics · Fermentation · Health · Nutritional